A Mediation Model to Explain HIV Antiretroviral Adherence Among Gay and Bisexual Men - Halkitis, Perry N. (2008)
Based on quantitative data describing a sample of 300 HIV seropositive gay and bisexual men living in New York City who were on antiretroviral drug therapy, variables of interest were collapsed into 4 latent constructs–SES (including health care provision), psychological states, drug use impairment, and HIV treatment adherence–and structural equation modeling was used to test the relations among them. Our model indicated a complex interplay between socioeconomic factors, drug use impairment, psychological states, and adherence. It is imperative for counselors and clinicians working with this population to understand the complex relationships between cultural, social, and psychological realities and adherence to HIV antiviral medications and to develop effective socially relevant and culturally nested interventions.